Guidelines for using evacuation shelters as a part of Beaufort Sea EER strategies ... - Barker, Anne; Timco, Garry; Wright, Brian (National Research Council of Canada, 2007)
With offshore exploration activity and the potential development of production platforms for offshore gas in the Canadian Beaufort Sea, issues related to proper Escape, Evacuation and Rescue (EER) systems are critical. Structures in the Beaufort Sea have unique requirements with respect to EER design and operation. The considerations for establishing an Evacuation Shelter (ES) on stable ice and the effects of the shoulder seasons on suitable EER systems in the Arctic may have a significant impact on receiving regulatory approval for operations. This area of study has been largely neglected in the past but it should be at the forefront of concerns for resource development in frontier regions. This report develops guidelines for establishing ES in the Canadian Beaufort Sea region of the Arctic. The authors have developed two decision-making flowcharts. The first helps decisionmakers evaluate whether an ES may be part of an overall EER strategy for a particular platform. The second flowchart aids in ...